Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/jbm.b.30060
|View full text |Cite
|
Sign up to set email alerts
|

Bone cement X‐ray contrast media: A clinically relevant method of measuring their efficacy

Abstract: It is important to compare different contrast media used in bone cement according to their ability to attenuate X-rays and thereby produce image contrast between bone cement and its surroundings in clinical applications. The radiopacity of bone cement is often evaluated by making radiographs of cement in air at an X-ray tube voltage of 40 kV. We have developed a method for ranking contrast media in bone cement simulating the clinical situation, by (1) choosing the same X-ray tube voltage as used in clinical wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
(17 reference statements)
1
27
0
Order By: Relevance
“…1 for numbers of specimens or replicates used for each type of testing). These determined properties are of clinical relevance [17,25,29,35,41,43,44]. (3) Using our determined values for the cement properties and an optimization method, we determined an appropriate xylitol amount.…”
Section: Methodsmentioning
confidence: 99%
“…1 for numbers of specimens or replicates used for each type of testing). These determined properties are of clinical relevance [17,25,29,35,41,43,44]. (3) Using our determined values for the cement properties and an optimization method, we determined an appropriate xylitol amount.…”
Section: Methodsmentioning
confidence: 99%
“…Due to this incompatibility with the polymeric matrix, the contrast forms a segregated phase and makes mixing of reagents more difficult during the preparation. For this reason, some authors have suggested the use of alternative contrasts, such as iodine (Almén, 1995;Davy et al, 1997;Davenport et al, 1999;Ginebra et al, 2002;Nakamura et al, 2003;Artola et al, 2004;Kjellson et al, 2004;Van Hooy-Corstjensa et al, 2004) and/or bismuth (Rawls et al, 1996;Deb et al, 2002) based compounds. These compounds are chemically linked to specially designed monomers and are thus automatically incorporated into the BC formulation.…”
Section: Verified That It Is Verymentioning
confidence: 99%
“…Other types of contrast media have previously been investigated to find contrast media which are as effective at providing X-ray attenuation [7] without reducing the mechanical properties or producing abrasive or inflammatory particles. Iohexol and Iodixanol are non-ionic water-soluble contrast media that are used extensively throughout the world, as solutions that are injected into the body for radiographic imaging [8].…”
Section: Introductionmentioning
confidence: 99%
“…The powder-based opac-ifier iodixanol (IDX) has previously been investigated in PMMA bone cement as an X-ray contrast media. The radiographic contrast study showed that equal concentrations, by weight, of IDX and ZrO 2 produce similar attenuation of X-rays under clinical X-ray measurement situations [7]. The in vitro and in vivo inflammation response was investigated [9] and it was found that the inflammatory response to cement containing IDX is lower than those for cements containing ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%